Pelatihan Dasar Coding Menggunakan Scratch sebagai Upaya Meningkatkan Keterampilan Abad 21 Siswa SMA Negeri 1 Bangkalan - Maharani, Aprilia; Khofifah, Retno Dwi; Umam, Rizka Alfinatul; Rayhan, Bilal; Affan, Andrian; Prameswari, Agil (Penerbit Widina, Widina Media Utama, 2025)
Technological developments require students to master 21st-century skills, including critical thinking, creativity, collaboration, and digital literacy. Scratch, a visual programming medium, offers an easy way to introduce basic coding concepts to beginners, making it relevant for use in digital empowerment-based community service programs. This activity aims to improve the basic understanding of programming and computational thinking skills of 10th-grade students at SMA Negeri 1 Bangkalan through a series of participatory activities. The implementation process includes material delivery, group work, digital project development practices, an educational quiz tournament, and a reflection session using a cooperative approach based on the Teams Games Tournament (TGT) model. The success of the activity was evaluated through observations of participant activity, assessment of the resulting Scratch work, quiz scores, and a questionnaire that reflected students' level of understanding and interest. A total of 37 students participated in this activity offline in the school's computer laboratory. The evaluation results showed that all participants were actively involved, the majority understood the basic concepts of Scratch, and 90% of groups successfully produced animations or simple games that worked well. In addition, 86% of students were able to explain the programming logic used, and 88% expressed interest in participating in follow-up activities. These findings indicate that the Scratch-based mentoring program has a positive impact on increasing students' creativity, collaboration, and learning motivation, and has the potential to be developed as a sustainable digital literacy strengthening activity.ABSTRAKPerkembangan teknologi menuntut siswa menguasai keterampilan abad ke-21, termasuk berpikir kritis, kreativitas, kolaborasi, dan literasi digital. Scratch sebagai media pemrograman visual menawarkan cara yang mudah untuk memperkenalkan konsep dasar coding kepada pemula, sehingga relevan digunakan dalam program pengabdian berbasis pemberdayaan digital. Kegiatan ini bertujuan meningkatkan pemahaman dasar pemrograman dan kemampuan berpikir komputasional siswa kelas X SMA Negeri 1 Bangkalan melalui serangkaian aktivitas yang disusun secara partisipatif. Proses pelaksanaan mencakup penyampaian materi, kerja kelompok, praktik pengembangan proyek digital, turnamen kuis edukatif, serta sesi refleksi dengan pendekatan kooperatif berbasis model Teams Games Tournament (TGT). Keberhasilan kegiatan dievaluasi melalui observasi keaktifan peserta, penilaian karya Scratch yang dihasilkan, perolehan skor kuis, serta angket yang menggambarkan tingkat pemahaman dan ketertarikan siswa. Sebanyak 37 siswa mengikuti kegiatan ini secara luring di laboratorium komputer sekolah. Hasil evaluasi menunjukkan seluruh peserta terlibat secara aktif, mayoritas memahami konsep dasar Scratch, dan 90% kelompok berhasil menghasilkan animasi atau gim sederhana yang berjalan baik. Selain itu, 86% siswa mampu menjelaskan logika pemrograman yang digunakan, dan 88% menyatakan ketertarikan untuk mengikuti kegiatan lanjutan. Temuan ini menunjukkan bahwa program pendampingan berbasis Scratch memberikan dampak positif terhadap peningkatan kreativitas, kolaborasi, dan motivasi belajar siswa, serta memiliki peluang untuk dikembangkan sebagai kegiatan penguatan literasi digital secara berkelanjutan.